A label-free and ratiometric fluorescent immunosensor by integrating CRISPR/Cas 12a and 3D DNA nanomachine - Yu Ling; Ya Bin Cui; Hong Ran Tao; Xue Zhen Dong; Hang Yan; Zhe Sun; Hong Qun Luo; Nian Bing Li (Talanta Open, 2023)
Sensitive, selective, especially label-free detection of disease relevant protein biomarkers is highly valuable for clinical diagnosis and disease process monitoring but remains a challenge. Herein, with prostate specific antigen (PSA) as a model target, we have designed a label-free ratiometric fluorescent immunosensor based on three-dimensional (3D) DNA walker and the powerful clustered regularly interspaced short palindromic repeat (CRISPR)/Cas system, with poly(thymine) templated Cu nanoclusters and DAPI as signals. The aptamer-linked activator DNA was designed to convert target recognition event into activate deoxyribonuclease activity of CRISPR/Cas12a system and further cleave oligonucleotides. The cleavage behavior leads to the quenching of copper nanoclusters and stagnation of the cascade amplification progress of 3D DNA nanomachine. The DNA machine is constructed from primer DNA and silica nanospheres loaded by double-stranded DNA (dsDNA) with prominent 3′ end, and movement of the primer DNA is powered by exonuclease (Exo) III via a burnt-bridge mechanism. Without primer DNA, the dyes (DAPI) were embedded in the complementary DNA and emit strong fluorescence. The practical applicability of the biosensor was demonstrated by assay of PSA in human serum with satisfactory result. In addition, this completely label-free method, reduced consumption of antibody, greatly simplify the procedures and saving cost.